COMPARATIVE PHYTOCHEMICAL ANALYSIS AND ANTIDIABETIC ACTIVITIES OF TENDER AND RIPENED COCONUT FRUIT PARTS - SUPRIYA SAHA; SANCHARI BHATTACHARYA; PRIYANKA RAY; PRAPTI CHAKRABORTY (Asian Journal of Pharmaceutical and Clinical Research, 2025)
Objective: Diabetes mellitus is a chronic metabolic disorder, which leads to a decrease in quality of life and even death. There are various treatments for diabetes available in the market, but they have several side effects. In the search for natural antidiabetic agents or medicinal plants, coconut (Cocos nucifera L.) is a suitable choice due to its lesser adverse effects. This study investigates and compares the phytochemical profile and antidiabetic activities of tender and ripened coconut parts (e.g., husk, water, and milk). Methods: Different quantitative and qualitative tests were conducted to identify various bioactive compounds like alkaloids, flavonoids, phenolics, tannins, etc., and antidiabetic potential was evaluated through α-amylase and α-glucosidase enzyme inhibition assays using in vitro models to evaluate glucose lowering potential. Results: Both quantitative and qualitative assays showed differences in bioactive substances in tender and ripened coconut fruit parts. The in-vitro antidiabetic activity also showed notable differences in glucose-lowering effects. Conclusion: Antidiabetic activity showed that both ripened and tender coconut husks had significant inhibition, which is comparable to the standard drug acarbose, showing strong antidiabetic potential. The ripened coconut husk showed IC50 value of 821.45 µg/mL for α-amylase and 1172.82 µg/mL for α-glucosidase while tender coconut husk showed 1079.11 µg/mL α-amylase for and 1196.76 µg/mL for α-glucosidase. Both the ripened and tender coconut milk showed low to minimal antidiabetic activity, while coconut water demonstrated moderate activity.